2008
DOI: 10.1108/10650740810849070
|View full text |Cite
|
Sign up to set email alerts
|

Improving service management in campus IT operations

Abstract: Purpose -This paper aims at presenting the benefits from implementing IT service management (ITSM) in an organization for managing campus-wide IT operations. In order to improve the fault correlation from business perspectives, we proposed a framework to automate network and system alerts with respect to its business service impact for proactive notification to IT operations management. Design/methodology/approach -The authors first evaluate the effect of IT service management (ITSM) tools in practical adoptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…CMMI is another method that ITSM researchers have applied to measure the maturity of ITSM (e.g., Park, Kim, Choi, & Jun, 2008;Richter, 2009;Deutscher & Felden, 2009;Dutton, 2010). Business Continuity Management (BCM) is also applied in ITSM studies (e.g., Lumpp et al, 2008;Wan & Chan, 2008;Wan, 2009). It provides a framework for managing risk in the event of disaster, by identifying the relationships between business services and IT resources.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…CMMI is another method that ITSM researchers have applied to measure the maturity of ITSM (e.g., Park, Kim, Choi, & Jun, 2008;Richter, 2009;Deutscher & Felden, 2009;Dutton, 2010). Business Continuity Management (BCM) is also applied in ITSM studies (e.g., Lumpp et al, 2008;Wan & Chan, 2008;Wan, 2009). It provides a framework for managing risk in the event of disaster, by identifying the relationships between business services and IT resources.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Most of the studies found cover part of the ITG practices, but most of them aim to develop a framework or a model for a particular reality. Some universities used ITIL as the main practice to implement ITG [23,[45][46][47], others include COBIT [19,48] or ISO/IEC 38500 [18].…”
Section: It Governance In Universitiesmentioning
confidence: 99%
“…Pollard and Cater- Achieve a more predictable infrastructure due to improved rigor during system changes; improved clarity in roles and responsibilities; reduction in system and service outages; improved coordination between functional teams; seamless end-to-end service; more documented and consistent ITSM processes across the organization; consistent logging of incidents; enhanced productivity; reduced costs; and improved customer satisfaction. Wan and Chan (2008) Avoid chaos in operations management and achieve a systematic process; improvement of service target and identification of the most-requested users and services. Kumbakara (2007) Increased IT predictability, efficiency, and service quality; reduced support costs; compliance with regulatory requirements; and better management of end-to-end IT services Cater- Steel, Tan, and Toleman (2006) Compliance with legal requirements; risk management; cost reduction; and customer satisfaction Hochstein, Tamm, and Brenner (2005, May) Increased client-service orientation and improved quality of IT services; better efficiency due to process standardization, optimization, and automation; and improved transparency and comparability through process documentation and monitoring…”
Section: Office Of Governmentmentioning
confidence: 99%